2012
DOI: 10.1021/ml300049d
|View full text |Cite
|
Sign up to set email alerts
|

Novel Carboxamide-Based Allosteric MEK Inhibitors: Discovery and Optimization Efforts toward XL518 (GDC-0973)

Abstract: The ERK/MAP kinase cascade is a key mechanism subject to dysregulation in cancer and is constitutively activated or highly upregulated in many tumor types. Mutations associated with upstream pathway components RAS and Raf occur frequently and contribute to the oncogenic phenotype through activation of MEK and then ERK. Inhibitors of MEK have been shown to effectively block upregulated ERK/MAPK signaling in a range of cancer cell lines and have further demonstrated early evidence of efficacy in the clinic for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 16 publications
4
114
0
1
Order By: Relevance
“…3A & S3A) (32). Importantly, the combined use of these agents elicited robust suppression of pAKT and pERK, as well as more robust suppression of pRPS6 and p4EB-P1 than that achieved with either single agent alone.…”
Section: Resultsmentioning
confidence: 99%
“…3A & S3A) (32). Importantly, the combined use of these agents elicited robust suppression of pAKT and pERK, as well as more robust suppression of pRPS6 and p4EB-P1 than that achieved with either single agent alone.…”
Section: Resultsmentioning
confidence: 99%
“…Results from an animal study imply that cobimetinib has higher concentrations in the tumor than in plasma and the brain [11], and that it remains in the tumor longer than in plasma [19].…”
Section: Pharmacokineticsmentioning
confidence: 98%
“…In vitro, the 50 % maximum inhibitory concentration for MEK1 was 0.9 nmol/L [11]. In vitro trials in MAPK-dysregulated cancer cells showed that cobimetinib is associated with inhibition of ERK1/2 phosphorylation; ERK1/2 activity is a key component of the MAPK pathway [5].…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…3.3) led to the hypothesis that targeting multiple points on the MAPK pathway may enhance antitumour activity [2]. Cobimetinib is a potent, highly selective, reversible inhibitor of MEK1 and MEK2 [3,11,12]. Cobimetinib potently inhibited phosphorylation of ERK in two murine xenograft models of BRAF V600 -mutated melanoma (melanoma cells harboured a BRAF V600D mutation and were PTEN deficient in one xenograft model and harboured a BRAF V600E mutation in the other xenograft model) [13].…”
Section: Pharmacodynamic Profilementioning
confidence: 99%